2009
DOI: 10.1038/jid.2008.391
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Dietary Magnesium Prevents Connective Tissue Mineralization in a Mouse Model of Pseudoxanthoma Elasticum (Abcc6−/−)

Abstract: Pseudoxanthoma elasticum (PXE) is an autosomal recessive multi-system disorder characterized by ectopic connective tissue mineralization, with clinical manifestations primarily in the skin, eyes and the cardiovascular system. There is considerable, both intra-and inter-familial variability in the spectrum of phenotypic presentation. Previous studies have suggested that mineral content of the diet may modify the severity of the clinical phenotype in PXE. In this study, we utilized a targeted mutant mouse (Abcc6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
85
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(91 citation statements)
references
References 19 publications
4
85
0
2
Order By: Relevance
“…Again, no difference in the mineralization between the mice administered K3-GSH and those KO magnesium content by five-fold has been shown to completely prevent the mineralization in this mouse model of PXE. 19 Based on the latter observations, clinical trials are currently being initiated to test the efficacy of magnesium supplementation of diet for the treatment of patients with PXE. Finally, preliminary studies testing oral phosphate binders have suggested that some of them may be effective in counteracting the progress of cutaneous involvement in these patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Again, no difference in the mineralization between the mice administered K3-GSH and those KO magnesium content by five-fold has been shown to completely prevent the mineralization in this mouse model of PXE. 19 Based on the latter observations, clinical trials are currently being initiated to test the efficacy of magnesium supplementation of diet for the treatment of patients with PXE. Finally, preliminary studies testing oral phosphate binders have suggested that some of them may be effective in counteracting the progress of cutaneous involvement in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…This in vitro system has been utilized to test the efficacy of a number of compounds potentially interfering with the mineralization process, including anti-mineralization factors fetuin-A and magnesium. 4,19 In this system, addition of vitamin K2 in three different concentrations (10,50 or 100 μg/mL) together with Pi to the culture medium did not interfere with the precipitation of calcium phosphate, as determined by direct chemical assay of calcium associated with the cell layer ( fig. 3b).…”
Section: Figure 2 Mineralization Of Vibrissae In Abcc6mentioning
confidence: 99%
“…They previously showed that high dietary magnesium prevented calcification [31]. Here, they show that low magnesium diet aggravates calcium deposition in the model for PXE.…”
Section: Mineralization In Pxe Mouse Model Can Be Modulated By Ggcx mentioning
confidence: 50%
“…The effects of changes in dietary phosphate, calcium, and magnesium on the mineralization process have been studied in Abcc6 −/− mice using calcification of the connective tissue capsule surrounding the vibrissae as an early phenotypic biomarker [31]. While changes in phosphate did not modify mineralization, enrichment in magnesium (fivefold) significantly reduced connective tissue mineralization in this mouse model of PXE.…”
Section: The Influence Of Diet On the Mineralization Processmentioning
confidence: 99%
“…ocular manifestations and altered redox balance) it is possible that the same recommendation can be valuable also for PXE (Lecerf & Desmettre, 2010), even though further investigations are required to support this hypothesis. By contrast, more promising perspectives, at least in the mouse model, seem to be represented by a diet supplemented with an excess of magnesium, although the mechanisms of reduced calcifications are still unknown LaRusso et al, 2009) and the effects of long-term treatments with high doses of magnesium in humans have not been yet investigated.…”
Section: Diagnosis and Treatmentsmentioning
confidence: 99%